Pendampingan Mengembangkan RPP Berbasis Tematik untuk Guru SD Kecamatan Sukamakmur Kabupaten Bogor Jawa Barat - Cecep Kustandi; Nurdin Ibrahim; Ahkmad Sadek (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
The main problem faced by elementary school teachers in SukamakmurSub district, Bogor Regency, to be able to apply learning with thematic approaches is the low quality of Lesson Plan used by teachers, so that an effort is needed to design, develop, utilize and evaluate Lesson Plan thematic  forElemtary School Teachers in Sub district Bogor Regency, West Java in a Community Service program. Through community service activities, solutions will be offered for the problems formulated above. The approach offered for the realization of the Community Service program is an empowerment model with the following steps: 1) Preparation Phase; 2) Assessment Phase; 3) Planning or Alternative Program Planning Phase; 4) Formulation Phase of the Action Plan; 5) Implementation Phase (Implementation) Program or Activity; 6) Evaluation Phase; and 7) Termination Phase. The implementation of the Community Service program was indeed carried out as an effort to empower elementary school teachers in SukamakmurSub district, Bogor Regency through training and mentoring activities for the development of Lesson Plan thematic-based which resulted in thematic-based RPPs that met theoretically feasible criteria; meet the eligible criteria in terms of format, content and appearance; have high applied or appropriate in learning. The evaluation was carried out on the community service activities of the Education Technology Study Program of the Faculty of Education, Jakarta State University, to see the extent of the increase in knowledge and skills of educators (Elemtary School teachers) in designing, developing, utilizing and evaluating Lesson Plan thematic-based.